melamore
melamore
12-07-2014
Mathematics
contestada
let f(x)=9x-2 and g(x)=-x+3. find f(g(x)).
Respuesta :
mariamikayla
mariamikayla
12-07-2014
[tex]f(g(x))=9(-x+3)-2 \\ f(g(x))= -9x+27-2 \\ f(g(x))= -9x+25[/tex]
Answer Link
Аноним
Аноним
13-07-2014
[tex]f(x)=9x-2;\ g(x)=-x+3\\\\f(g(x))=9(-x+3)-2=-9x+27-2=-9x+25[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 26+ )
Otras preguntas
is -2 more than -1? or is it the other way around
which historical events are in the correct chronological order? crusades - renaissance - neolithic revolution - roman empire
What does the word vulnerable mean? 1. vulgar 2. guarded 3. unprotected 4. shocking
Bailey Manufacturing Co.'s static budget at 10,000 units of production includes $60,000 for direct labor and $6,000 for electric power. Total fixed costs are $2
Which is composed of alkenes? welding torch fuel polystyrene cups gasoline synthesized dyes
Write the equation of the following circle in general form and standard form. Show your work.
How would I set this to 0?
Contrast is the arrangement_______ elements in a composition?
Titrations provide a method of quantitatively measuring the concentration of an unknown solution. a. Trueb. False
answered PLSSS HELPPPP I WILLL GIVE YOU BRAINLIEST!!!!!! PLSSS HELPPPP I WILLL GIVE YOU BRAINLIEST!!!!!! PLSSS HELPPPP I WILLL GIVE YOU BRAINLIEST!!!!!! PLSSS H